Comparative Efficacy of Twice and Thrice Daily Colistin Administration in Critically Ill Patients Battling Multi-Drug Resistant Gram-Negative Infections: An Observational Study - Mohammed Valiyakath Hydross1; Sameer Abdul Samad2, 5*; Mahesh Balakrishna Savitri3; Ashish Datt Upadhyay4 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Colistin, a polymyxin antibiotic often reserved for treatment of multidrug-resistant Gram-negative infections, exhibits a narrow therapeutic index. Careful consideration of the pharmacokinetic (PK) and pharmacodynamic (PD) parameters of colistin is essential to maximize its efficacy and minimize toxicity. Both thrice-daily and twice-daily administration regimens have been employed, with critically ill patients posing unique challenges regarding colistin's PK/PD. Methods: This retrospective observational study compared the mortality rates, cure rates, length of hospital stay, nephrotoxicity, and readmission rates associated with thrice-daily and twice-daily administration of a fixed total daily dose of 9 million international units (MIU) of colistin in 151 critically ill patients with multidrug-resistant Gram-negative infections. Propensity score matching with a 1:5 case-control ratio was performed using XLSTAT software (by Addinsoft), and outcomes were analysed using logistic regression analysis. Results: Thrice-daily dosing of colistin was recorded in 125 patients, and twice-daily dosing in 26 patients. A total of 73 patients were included in the final analysis after propensity score matching. The 28-day mortality rates, clinical cure rates, and microbiological failure rates were comparable between the two groups (Odds ratio (OR) [95% confidence-interval (CI)] = 0.48 [0.07-3.46], P=0.467; 1.67 [0.31-8.90], P=0.548; 0.13 [0.001-19.5], P = 0.428, respectively). Hospital readmission rates within 90 days (OR [95% CI] = 1.05 [0.12-9.10], P=0.964) and duration of hospital stay (Beta coefficient = 1.55, P=0.683) were also comparable between the two groups. The incidence of nephrotoxicity-related AKI events during Colistin therapy was significantly lower with the 4.5 MIU twice-daily regimen (OR [95% CI] = 0.04 [0.004-0.35], P=0.004). Conclusion: Twice-daily colistin administration significantly reduces the risk of nephrotoxicity-related AKI events compared to thrice-daily administration in critically ill patients with multidrug-resistant Gram-negative infections.